2015
DOI: 10.1016/j.oceaneng.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

L1 Adaptive depth and pitch control of an underwater vehicle with real-time experiments

Abstract: This paper proposes a new control scheme for underwater vehicles. These systems are highly nonlinear and they often operate in a varying environment. A robust controller is therefore needed to deal with these challenges. The recently developped L 1 adaptive controller is proposed to be designed and implemented in real time for the first time on an underwater vehicle. Different experimental scenarios are then conducted to test the performance of the closed-loop system in two degrees of freedom. An interesting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…To deal with this problem, the work in Kaminer et al (2010) suggests augmenting the inner‐loop controllers with “Ł1 adaptive controllers,” that aim at eliminating the effect of inner‐loop uncertainty on the total path following system. See Maalouf et al (2015) and Xu et al (2021) for applications of this strategy to an underwater robot and a surface ship, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…To deal with this problem, the work in Kaminer et al (2010) suggests augmenting the inner‐loop controllers with “Ł1 adaptive controllers,” that aim at eliminating the effect of inner‐loop uncertainty on the total path following system. See Maalouf et al (2015) and Xu et al (2021) for applications of this strategy to an underwater robot and a surface ship, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Remark 1. Unlike the background work carried out in 12 , the underwater vehicle doesn't have a slow dynamic. Also, the Coriolis term C(v) is non-zero and the damping matrix is considered as a combination of linear and non-linear damping, i.e.…”
Section: Nonlinear Dynamic and Kinematic Modelmentioning
confidence: 99%
“…The problems are originated from the intrinsic time-varying and high level of nonlinearities, resulting from the hydrodynamic effects and the high level of external disturbance, caused by the sea currents and the drag effects acting on the vehicle 6,7 . To overcome these problems, various control methods have been proposed in the literature such as adaptive RISE 8 , feedback linearization controller 9 , output feedback control 10 , L 1 adaptive controller 11,12 , and adaptive fuzzy control 13 , Lyapunov-based model predictive control 14 , robust H ∞ control 15 , fuzzy backstepping sliding mode control 16 . A more detailed review of the proposed controllers for AUVs can be found in 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Input saturation, a challenge posed by actual actuators in AUVs, is managed through techniques like direct design 45 and anti‐windup compensation (AWC) 46 . The research landscape further extends to second‐order pitch‐axis models for AUVs, 47 multi‐input multi‐output H$$ {H}_{\infty } $$ control for yaw and pitch channels, 48 L1$$ {L}_1 $$ Adaptive control for depth and pitch models, 49 genetic algorithm‐optimized proportional‐integral controllers for yaw channels, 50 robust fractional‐order proportional‐integral‐derivative (FOPID) control for yaw channels, 51 robust H$$ {H}_{\infty } $$ control and μ$$ \mu $$ synthesis for pitch axes under parametric uncertainties and disturbances, 52,53 delayed output observer‐based SMC for pitch and yaw channels to compensate for variations in hydrodynamic parameters and measurement delays, 54,55 model reference adaptive proportional‐integral‐derivative controllers with AWC to address actuator saturation and uncertainties in AUVs 56,57 . Motivated by this extensive literature, this article explores the feasibility of a robust backstepping SMC approach for managing pitch and yaw channel dynamics in AUVs.…”
Section: Introductionmentioning
confidence: 99%